Manfaat Terapi Suportif dalam Mengurangi Kecemasan pada Siswa Korban Perilaku Bullying - Ikhwanudin Ikhwanudin; Novy Helena Catharina Daulima; Yossie Susanti Eka Putri (Jurnal Keperawatan Silampari, 2023)
This study aims to analyze the benefits of supportive therapy in reducing anxiety in students who are victims of bullying behavior. The research method used was a systematic review through article searches adjusted to formulating research questions with the PICO formula in the ProQuest, EBSCOhost, SpringerLink, ScienceDirect, and Clinicalkey for Nursing databases. The results showed that supportive therapy effectively reduced anxiety in students who were victims of bullying behavior. In conclusion, supportive treatment has proven effective as an intervention in reducing stress in students who are victims of bullying behavior. Keywords: Bullying, Anxiety, Supportive Therapy